2020
DOI: 10.1029/2020gl088865
|View full text |Cite
|
Sign up to set email alerts
|

Proglacial Lakes Control Glacier Geometry and Behavior During Recession

Abstract: Ice-contact proglacial lakes are generally absent from numerical model simulations of glacier evolution, and their effects on ice dynamics and on rates of deglaciation remain poorly quantified. Using the BISICLES ice flow model, we analyzed the effects of an ice-contact lake on the Pukaki Glacier, New Zealand, during recession from the Last Glacial Maximum. The ice-contact lake produced a maximum effect on grounding line recession >4 times further and on ice velocities up to 8 times faster, compared to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 72 publications
(83 reference statements)
1
56
0
Order By: Relevance
“…On a meso-scale, lake temperature affects subglacial hydrology (Carrivick et al, 2017;Stubblefield et al, 2019). On a macro scale (hundreds to thousands of meters) lake water temperature will affect the shape of the floating underside of a glacier and potentially also affect the shape of the entire terminus tongue (Sugiyama et al, 2019;Sutherland et al, 2020; Figure 2). Subglacial hydrology is affected by lake water temperature at all scales.…”
Section: Lake Water Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…On a meso-scale, lake temperature affects subglacial hydrology (Carrivick et al, 2017;Stubblefield et al, 2019). On a macro scale (hundreds to thousands of meters) lake water temperature will affect the shape of the floating underside of a glacier and potentially also affect the shape of the entire terminus tongue (Sugiyama et al, 2019;Sutherland et al, 2020; Figure 2). Subglacial hydrology is affected by lake water temperature at all scales.…”
Section: Lake Water Temperaturementioning
confidence: 99%
“…Representing the impact of short-lived (decadal) accelerations and decelerations of a glacier in response to ice-marginal lake effects (Sutherland et al, 2020) is difficult within a longer (millennial) glacier evolution model, and not least because those effects might not simply average out. Being able to perform long simulations over large spatial extents must contend with lake size being highly sensitive to the size and position of lake overspill channels, which are on a scale of 10-100 m.…”
Section: Spatio-temporal Variability and Boundary Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of many supraglacial lakes and ponds are governed by filling and draining cycles, and hydrological connectivity that are controlled by glacier surface and internal structures (Benn et al, 2001(Benn et al, , 2017Wessels et al, 2002;Miles et al, 2017). Studies also found that proglacial lakes also have a significant control on the glacier dynamics (Sutherland et al, 2020). These processes have only been studied on a handful of glaciers in the field, and there are still many processes and feedbacks that need to be investigated.…”
Section: Supraglacial Water Bodies and Ice Cliffsmentioning
confidence: 99%